Penerapan Model Pembelajaran Kooperatif Think Pair Share dan Numbered Head Together dalam Pembelajaran Bahasa Arab - Isnaini, Faizzatin; Safitriani, Ida; Dariyadi, Moch. Wahib (Kalimatuna: Journal of Arabic Research, 2024)
Arabic is regarded as a foreign language by the majority of Indonesians, and students often find it challenging to learn. To enhance students' Arabic language skills, cooperative learning models such as Think-Pair-Share (TPS) and Numbered Heads Together (NHT) have been implemented. This study utilizes a library research method to gather theoretical support for the effectiveness of these models. The TPS and NHT approaches have been shown to improve students' proficiency in Arabic. Research findings indicate that students respond positively to these methods, as they foster an active, enjoyable, and collaborative learning environment. Observations reveal a significant enhancement in students' skills upon the implementation of TPS and NHT. These results demonstrate that TPS and NHT are effective strategies for teaching Arabic and have the potential for broader application in foreign language education.